2017
DOI: 10.1080/15427560.2017.1308941
|View full text |Cite
|
Sign up to set email alerts
|

Disposition Effect and Diminishing Sensitivity: An Analysis Based on a Simulated Experimental Stock Market

Abstract: We experimentally investigate the existence of the disposition effect and diminishing sensitivity as its potential cause. Our approach includes three key characteristics: (i) An environment closely resembling actual stock markets; (ii) Individual-specific reference prices; (iii) A direct test of diminishing sensitivity as a cause of the disposition effect. We find strong support for the existence of the disposition effect as an independent hypothesis. This is an improvement over previous studies, which tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…As Odean (1998Odean ( , p. 1782 In a post-experimental questionnaire, we elicit subjects' most likely reference price and find that it is the average price (see the online appendix). This approach is also used in Kohsaka et al (2013), with similar results. Therefore, we shall use the weighted average reference price to calculate both PGR and PLR throughout the paper.…”
Section: Resultsmentioning
confidence: 84%
“…As Odean (1998Odean ( , p. 1782 In a post-experimental questionnaire, we elicit subjects' most likely reference price and find that it is the average price (see the online appendix). This approach is also used in Kohsaka et al (2013), with similar results. Therefore, we shall use the weighted average reference price to calculate both PGR and PLR throughout the paper.…”
Section: Resultsmentioning
confidence: 84%
“…Although 40 years have passed, Kahneman and Tversky's (1979) prospect theory, one of the milestones of behavioral finance, continues to be approached extensively in academia, as do heuristics, biases, and the disposition effect. Current articles dealing with the prospect theory and adding other elements include those by Jiao (2017) and Kohsaka et al (2017).…”
Section: Behavioral Finance: Background and Consolidationmentioning
confidence: 99%
“…Indeed, Li and Yang (2013) and Kohsaka et al . (2017) found that people with stronger risk‐seeking propensity display a stronger disposition effect. Meanwhile, Shumway and Wu (2006) empirically analyzed Shanghai stock exchange traders and found that traders who display a disposition effect earn lower profits.…”
Section: Appendix Bmentioning
confidence: 99%